Back Cover: Deracemization of Secondary Alcohols by using a Single Alcohol Dehydrogenase (ChemCatChem 8/2016). Issue 8 (22nd April 2016) - Karume, Ibrahim; Takahashi, Masateru; Hamdan, Samir M.; Musa, Musa M.
Abstract : The Cover shows a single‐enzyme‐mediated two‐step approach for deracemization of secondary alcohols. In their Communication, I. Karume et al. demonstrate how a single mutant of Thermoanaerobacter ethanolicus secondary alcohol dehydrogenase enables the nonstereoselective oxidation of racemic alcohols to ketones, followed by a stereoselective reduction process. This enzyme was utilized for the deracemization of secondary alcohols with up to >99 % ee and >99.5 % recovery in one pot, without the need to isolate the prochiral ketone intermediate. More information can be found in the Communication by I. Karume et al. onpage 1459 in Issue 8, 2016 (DOI:10.1002/cctc.201600160 ).